2013
DOI: 10.1039/c3cp00095h
|View full text |Cite
|
Sign up to set email alerts
|

On the radical scavenging activity of isoflavones: thermodynamics of O–H bond cleavage

Abstract: We have performed Density Functional Theory B3LYP/6-311++G** calculations of reaction enthalpies of antioxidant action mechanisms for nine isoflavones. O-H bond dissociation enthalpies, ionization potentials, proton dissociation enthalpies, proton affinities and electron transfer enthalpies related to Hydrogen Atom Transfer (HAT), Single Electron Transfer-Proton Transfer (SET-PT) and Sequential Proton-Loss Electron-Transfer (SPLET) mechanisms were investigated in gas- and solution-phases. Studies on the radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 54 publications
9
53
0
Order By: Relevance
“…of clovamides. A considerable anti-free radical activity has been found for daidzein (Cai et al, 2012), genistein (Cai et al, 1997), and other isoflavones (Lengyel et al, 2013). The presence of clovamides (caffeic acid esters) in T. alexandrinum extract may additionally enhance its free radical scavenging action.…”
Section: Discussionmentioning
confidence: 99%
“…of clovamides. A considerable anti-free radical activity has been found for daidzein (Cai et al, 2012), genistein (Cai et al, 1997), and other isoflavones (Lengyel et al, 2013). The presence of clovamides (caffeic acid esters) in T. alexandrinum extract may additionally enhance its free radical scavenging action.…”
Section: Discussionmentioning
confidence: 99%
“…In general, three independent pathways of the antioxidant activity of phenolic compounds (ArOH) were described [2, 3,6] and they are outlined in Scheme 1. The hydrogen atom transfer (HAT) represents the single step radical termination via OAH bond homolytic splitting-off.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in accordance to the experimental work of Musialik et al (2009), where the authors observed that in ionization supporting solvents, SPLET runs in ring A via deprotonation of 7-OH group of quercetin and HAT/SET-PT occurs from 3',4'-dihydroxy moiety. In the case of isoflavones (Lengyel et al 2013), the situation is very simple: in all environments, the lowest PA values were obtained exclusively for 7-OH groups. This indicates that ring A can play significant role in the SPLET reaction pathway.…”
Section: Flavonoidsmentioning
confidence: 99%
“…In water, very large drop in PAs was observed, all values are considerably lower than BDEs. Therefore, in water, SPLET represents the thermodynamically preferred mechanism, followed by HAT and SET-PT , Lengyel et al 2013). Here, one should keep in mind that these studies are focused on the thermodynamic preference of studied compounds to enter individual reaction pathways and the dominating process may depend on the type of scavenged free radical.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation